SUCROSE TRANSPORTER 5 supplies Arabidopsis embryos with biotin and affects triacylglycerol accumulation. (31st December 2012) - Pommerrenig, Benjamin; Popko, Jennifer; Heilmann, Mareike; Schulmeister, Sylwia; Dietel, Katharina; Schmitt, Bianca; Stadler, Ruth; Feussner, Ivo; Sauer, Norbert
Summary The Arabidopsis SUC5 protein represents a classical sucrose/H+ symporter. Functional analyses previously revealed that SUC5 also transports biotin, an essential co‐factor for fatty acid synthesis. However, evidence for a dual role in transport of the structurally unrelated compounds sucrose and biotin in plants was lacking. Here we show that SUC5 localizes to the plasma membrane, and that the SUC5 gene is expressed in developing embryos, confirming the role of the SUC5 protein as substrate carrier across apoplastic barriers in seeds. We show that transport of biotin but not of sucrose across these barriers is impaired in suc5 mutant embryos. In addition, we show that SUC5 is essential for the delivery of biotin into the embryo of biotin biosynthesis‐defective mutants (bio1 and bio2). We compared embryo and seedling development as well as triacylglycerol accumulation and fatty acid composition in seeds of single mutants (suc5, bio1 or bio2), double mutants (suc5 bio1 and suc5 bio2) and wild‐type plants. Although suc5 mutants were like the wild‐type, bio1 and bio2 mutants showed developmental defects and reduced triacylglycerol contents. In suc5 bio1 and suc5 bio2 double mutants, developmental defects were severely increased and the triacylglycerol content was reduced to a greater extent in comparison to the single mutants. Supplementation with externally applied biotin helped to reduce symptoms in both single and double mutants, but the efficacy of supplementation was significantly lower in double than in single mutants, showing that transport of biotin into the embryo is lower in the absence of SUC5.